The Comparative Study on the Damage Zones of Cylindrical and Spherical Charges in Rock and Soil - Qian Xu; Zhong-Qi Wang (Shock and Vibration)
To compare the damage zones of spherical and cylindrical charges in rock and soil, a quasistatic spherical model was established to predict the characteristic dimension of the cavity. The results indicated that the damage zones of cylindrical charges were larger than those of spherical charges. Furthermore, the cavity development of two charges with different shapes was obtained by numerical simulation, and a comparison of the prediction results between the quasistatic model and numerical simulation was made. The comparison showed that the model could predict the damage zones exactly and faster than numerical simulation. Ultimately, the influence of explosions and soil media was discussed by the quasistatic model. It was observed that larger damage zones were generated by smaller values of the product of pressure and exponential expansion. However, the influence of soil media was complex, and larger damage zones were usually generated by the harder soil media.